A combined methodology for the hydraulic rehabilitation of urban drainage networks. Issue 6 (17th August 2016) - Gaudio, Roberto; Penna, Nadia; Viteritti, Valerio
Abstract : During medium and high intensity storm events, urban drainage networks can rapidly reach their maximum capacity, and subsequently floods can occur. Owing to the non-linearity of the processes involved, it is evident that the return period of a rainfall is different from the return period of the generated overflows. Therefore, the assessment of the maximum overflow volume related to a given return period is a key element in the management of urban drainage networks, since it may cause problems to infrastructure and economic losses. In this paper, a combined methodology for the hydraulic rehabilitation of such networks is proposed, by expressing their hydraulic critical conditions in terms of overflow volumes rather than rainfall volumes and considering both observed rainfall data and synthetic hyetographs derived from statistical analysis. The first application of the proposed methodology to the sewer network of the Mesola Municipality is presented and commented on.